Effect of Recognition and Career Advancement on Employee Job Performance: A Study of Nigerian Brewery Plc. Imagbon, Ijebu- Ode, Ogun State - Afolabi, Michael Oluseye; Essien, Adebolaji Ekong; Ogunsola, Modupe Omowunmi (Business Management and Strategy, 2022)
The purpose of this study is to explore the effect of recognition and career advancement on employee job performance in Nigeria Brewery Plc in Imagbon, Ijebu Ode, Ogun State. Survey research design was adopted for the study. The target population consists of 215 staff of Nigerian Brewery Plc. Imagbon, and sample size was 88. A structured questionnaire was used as a research instrument in gathering the primary data used for the study. The data collected were analyzed using mean, standard deviation and correlation analysis with the help of Statistical Package for Social Science (SPSS version 23). The results and findings indicated that employee recognition (r-0.759, p- 0.029) and career advancement (r-0.594, p- 0.012) have significant and positive effects on employee job performance in Nigerian Brewery Plc Imagbon, Ijebu Ode, Ogun State. The research recommends that the management of Nigerian brewery Plc should put a measure in place to ensure retention of younger employees that constitute the greater percentage of the brewery industry through adequate employee recognition programmes; and that management should be fully committed to employee flexible work schedule and provide an enabling environment for all and sundry within the organization.